Kompetencje komunikacyjne nauczycieli - Strykowska-Nowakowska, Justyna (Studia Edukacyjne, 2017)
The article discusses the problem of teachers’ communicative competences and presents it from both the theoretical and empirical perspective. The first part of the article helps understand the communication process and defines teachers’ communicative styles at school and barriers for pedagogical communication. The second part presents the results of diagnostic research on selected teachers’ communicative competences. The research problems included: How do teachers understand the communication process at school, and what are the factors determining its level? What communicative styles do teachers use? What are the barriers in communication between teachers and students? The article concludes with remarks and postulates.